2020
DOI: 10.3389/fcvm.2020.585692
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Myocardial Fibrosis in Intensive Endurance Training Athletes: A Systematic Review and Meta-Analysis

Abstract: Objective: To review the published literature reporting on the incidence of myocardial fibrosis (MF) in high-intensity endurance athletes measured by late gadolinium enhancement (LGE) with cardiac magnetic resonance imaging (CMR). Methods: Five databases (PubMed, Cochrane Controlled Trials Register, EMBASE, Web of Science, and SPORTDiscus) were searched to obtain case cohort studies published before November 10, 2019. From 96 abstracts or reports extracted, 18 full-text articles were reviewed. The incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 37 publications
1
13
1
1
Order By: Relevance
“…All available evidence indicates that the prevalence of MF, as documented by LGE in CMR scans, is significantly higher in athletes compared to sedentary controls. The pooled frequency of 16.6% is lower than the 21.1% reported by Zhang et al (16), with the difference owed to the updated set of studies, which include new data, updated numbers from some research teams and exclude some previous, non-peer-reviewed datasets.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…All available evidence indicates that the prevalence of MF, as documented by LGE in CMR scans, is significantly higher in athletes compared to sedentary controls. The pooled frequency of 16.6% is lower than the 21.1% reported by Zhang et al (16), with the difference owed to the updated set of studies, which include new data, updated numbers from some research teams and exclude some previous, non-peer-reviewed datasets.…”
Section: Discussioncontrasting
confidence: 57%
“…Although the underlying mechanisms are widely undetermined, the summarized evidence supported genetic predisposition, silent myocarditis, pulmonary artery pressure overload, and prolonged exercise-induced repetitive micro-injury as possible contributors (15). More recently, Zhang et al (16) performed a meta-analysis of athletic individuals and sedentary controls who underwent CMR, focusing however only on general MF prevalence without looking into different patterns, and without discriminating different athletic age groups, or sex-specific data. According to the results, 21.1% of athletes had evidence of LGE, compared to just 3.2% in sedentary controls.…”
Section: Systematic Review Systematic Review Rationale-objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were corroborated in the present study; when runners were divided into tertiles, the largest risk reduction was found in the first tertile, although no U-trend was observed. In the context of the U-trend [ 21 ], it is notable that there are data suggesting an increased incidence of atrial fibrillation [ 22 ], a disease associated with both heart failure and cardioembolic stroke, myocardial fibrosis [ 23 ] and, infrequently, arrhythmogenic sudden death [ 24 ] in those involved in extreme physical activities. The greatest mortality benefit was reported to be achieved for individuals who were running and engaged in some other physical activity [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exercise-induced myocardial fibrosis patterns are various and differ according to the age of the athletes [ 61 , 62 , 63 ]. Fibrosis is often found near the interventricular septum, especially in middle-aged and older athletes, and near the right ventricular insertion points, mainly in young athletes [ 4 , 5 , 61 ].…”
Section: Introductionmentioning
confidence: 99%